ANALISIS FAKTOR PENYEBAB LESBI DI SMA X KOTA PADANG - Emeliya Hardi; Rina Yulitri (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This research is motivated by a case that leads to lesbian behavior in SMA X in Padang. This study aims to determine the factors behind a person becoming a lesbian in SMA X in Padang. This research is a qualitative case study involving two female students who became lesbians. Data collection techniques using observation and interviews. Analysis of the data used in this research is descriptive qualitative and then triangulated data from different sources. The results showed that the factors behind someone becoming a lesbian in SMA X in Padang were, 1) the factors of parenting parents who were too authoritarian and permissive, 2) the trauma factors in past life, 3) social environmental factors, 4) lack of religious knowledge well.